(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article proposes a revision at Bertolt Brecht as a central reference in the conformation of our imaginary of a political theater and an engaged pedagogy. Starting from a discussion of the reified or mystified dimension of this figure, it proposes as lines of flight readings of Brechtian experiences with the political theater of the Russian avant-garde, as well as of Heiner Müller’s reflections and criticisms of the learning play. The recognition of a Brecht who is more subversive than revolutionary does not diminish the importance of the Brecht myth as an idea-force that gives impetus to various political processes of scenic creation, but rather places it outside the function of being a model of a necessarily positive hope.